2015
DOI: 10.1007/s11250-015-0824-5
|View full text |Cite
|
Sign up to set email alerts
|

Serological prevalence of contagious bovine pleuropneumonia in agro-pastoral areas of Nigeria

Abstract: CBPP is endemic to agro-pastoral areas, and it is doubtful if the current control strategies are making real impact in reducing production losses. Although eradication is more likely to be achieved through regional approaches, enhanced vaccination coverage supported with targeted surveillance and a trace back system based on cattle trade and movement records will sustain effective control of the disease in the Nigerian cattle population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…Pastoralists reported 72% herd prevalence and 6.4% individual prevalence of CBPP in this study. This herd prevalence was higher than previously reported [ [58] , [59] , [60] , 78 ]), indicating that CBPP is a serious problem in this area. However, individual prevalence was lower as pastoralists only report active, clinical infections whereas sero-prevalence methods in published reports detect any exposure to the pathogen, whether from previous or active, clinical or subclinical infections.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Pastoralists reported 72% herd prevalence and 6.4% individual prevalence of CBPP in this study. This herd prevalence was higher than previously reported [ [58] , [59] , [60] , 78 ]), indicating that CBPP is a serious problem in this area. However, individual prevalence was lower as pastoralists only report active, clinical infections whereas sero-prevalence methods in published reports detect any exposure to the pathogen, whether from previous or active, clinical or subclinical infections.…”
Section: Discussioncontrasting
confidence: 68%
“…CBPP was not included in the diagnostic survey since problems with CBPP were not previously reported in the study area. Several independent studies have indicated 27%–55% herd prevalence and 14–30% individual prevalence of CBPP amongst pastoral cattle in Nigeria [ [58] , [59] , [60] , 78 ]. Pastoralists reported 72% herd prevalence and 6.4% individual prevalence of CBPP in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agro-pastoral areas of Nigeria, the prevalence of CBPP at the flock level was 54.7%, and the proportion of animals with a monoclonal antibody MmmSC detected using of c-ELISA, was 30.2% ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arthritis rather than pulmonary symptoms are characteristic features of the disease in affected calves [5,8]. In different parts of Africa, varying prevalence of CBPP was reported ranging from 4 to 63%, affecting the economies of these countries [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%